LEGAL PROVIDING PROBLEMS IN USING THE NEWEST TECHNOLOGIES - Trynova, Yana (SUPREMANCE OF LAW, 2017)
This article focuses on one type of newest technology - nanotechnology. A concept of nanotechnology and the scope of their use. Feature article is parting the emphasis on the negative aspects of this innovation. Points to the gaps in the various branches of the Ukrainian law with regard to the establishment of the safe use of nanotechnology. Such state laws pose a real threat to the disappearance of all ecosystem, part of which is the people. The article given a vector followed by research in the field of integrated legal support nanotechnology.